Effect of Antisense Oligodeoxynucleotide of Vascular Endothelial Growth Factor C on Lymphangiogenesis and Angiogenesis of Pancreatic Cancer - 李凯 陶京 李弢 许州 杨智勇 吴河水 熊炯断 王春友 (Journal of Huazhong University of Science and Technology. Medical sciences, 2007)
In order to investigate the effect of antisense oligonucleotide （ASODN） of vascular endothelial growth factor C （VEGF-C） on lymphangiogenesis and angiogenesis of pancreatic cancer, antisense and scamble-sense oligonucleotide of VEGF-C were constructed, and the model of nude mice with orthotopically xenografied human pancreatic cancer cells （Panc-1） was established. Thirty nude mice were randomly divided into 3 groups： PBS control group （group A）, scramble-sense control group （group B） and antisense group （group C）. All nude mice were treated once every 2 days as 3 times per week, for 3 weeks （oligonucleotide 10 mg/kg every time）. After treatments were completed, ELISA method was used to examine the concentration of VEGF-C in plasma and immunohistochemical method to examine microvessel density （MVD）, lymphtic vessel density （LVD） of pancreatic cancer. The results showed that the expression of VEGF-C was inhibited significantly in group C. The concentrations were 237.5±41.5, 221.5±52.3 and 108.6±14.9 pg/mL in groups A, B and C respectively （P〈0.01）. LVD in groups A, B and C was 13.8±2.1, 12.4±1.9 and 4.2±1.6 respectively （P〈0.01）. MVD in groups A, B and C was 27.5±8.7, 25.9±4.2 and 19.4±5.6 respectively with no significant difference among the groups （P〉0.05）. It was suggested that VEGF-C ASODN decreased the expression levels of VEGF-C in nude mice with orthotopically xenografted human pancreatic cancer, and it could inhibit lymphangiogenesis, but had no significant effect on angiogenesis.